2012
DOI: 10.1111/j.1540-4560.2012.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Discrimination at Work: The Use of Field Experiments

Abstract: Antidiscrimination law offers protection to workers who have been treated unfairly on the basis of their race, gender, religion, or national origin. In order for these protections to be invoked, however, potential plaintiffs must be aware of and able to document discriminatory treatment. Given the subtlety of contemporary forms of discrimination, it is often difficult to identify discrimination when it has taken place. The methodology of field experiments offers one approach to measuring and detecting hiring d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 36 publications
(33 reference statements)
0
65
0
1
Order By: Relevance
“…Researchers acknowledge that this assessment of additional fictitious applications poses a burden on the employers' time (e.g. Pager & Western, 2012) and most research designs in correspondence testing limit the burden that is being placed on one employer. Usually a company is only considered once, even if more vacancies fitting the requirements of the researchers are published during the testing time, and the number of fictitious applications is limited, usually to two or three applications per company.…”
Section: Employers' Rights -Avoiding Harm and Maintaining The Confidementioning
confidence: 99%
“…Researchers acknowledge that this assessment of additional fictitious applications poses a burden on the employers' time (e.g. Pager & Western, 2012) and most research designs in correspondence testing limit the burden that is being placed on one employer. Usually a company is only considered once, even if more vacancies fitting the requirements of the researchers are published during the testing time, and the number of fictitious applications is limited, usually to two or three applications per company.…”
Section: Employers' Rights -Avoiding Harm and Maintaining The Confidementioning
confidence: 99%
“…The sociological evidence on discrimination which they collected came from three sources: (1) studies of the agents of discrimination, using qualitative or concealed methodologies; (2) statistical analyses of income and employment profiles of minorities, controlling for educational achievements, to judge whether systematic discrimination might have taken place; (3) quasi-experimental studies using "situation testing" (e.g., actors, playing the role of minority applicants; and/or applying for advertised jobs using "correspondence testing" by submitting job applications in which the ethnicity of the applicant, e.g., European-American, or African-American) was manifest. Pager and Western in 2012 [14] using both correspondence and situation testing, further showed that discrimination against African-Americans remained marked.…”
Section: Studying Discrimination: Methodological Issues and Results mentioning
confidence: 99%
“…Even if Social Darwinism is not the law of the land, racial discrimination persists, with tragic consequences (Reskin 2012). We see this in audit studies revealing discrimination in housing (Ondrich, Stricker, and Yinger 1999), employment (Pager and Western 2012), and even shopping online (Doleac and Stein 2010); we see it in policing practices (Kochel, Wilson, and Mastrofski 2011) and incarceration policies (Kutateladze et al 2014); and we see it in policy debates over economic development in poor countries. A Troublesome Inheritance adds fuel to contemporary racism, with the trappings of genomic science.…”
Section: Genetic Taboosmentioning
confidence: 95%